Sex differences in traumatic brain injury: a multi-dimensional exploration in genes, hormones, cells, individuals, and society - Cheng Ma; Xin Wu; Xiaotian Shen; Yanbo Yang; Zhouqing Chen; Xiaoou Sun; Zhong Wang (Chinese Neurosurgical Journal, 2019)
Abstract Traumatic brain injury (TBI) is exceptionally prevalent in society and often imposes a massive burden on patients’ families and poor prognosis. The evidence reviewed here suggests that gender can influence clinical outcomes of TBI in many aspects, ranges from patients’ mortality and short-term outcome to their long-term outcome, as well as the incidence of cognitive impairment. We mainly focused on the causes and mechanisms underlying the differences between male and female after TBI, from both biological and sociological views. As it turns out that multiple factors contribute to the gender differences after TBI, not merely the perspective of gender and sex hormones. Centered on this, we discussed how female steroid hormones exert neuroprotective effects through the anti-inflammatory and antioxidant mechanism, along with the cognitive impairment and the social integration problems it caused. As to the treatment, both instant and long-term treatment of TBI requires adjustments according to gender. A further study with more focus on this topic is therefore suggested to provide better treatment options for these patients.